Anti-human Vascular Endothelial Growth Factor (VEGF) Antibody Selection for Immunohistochemical Staining of Proliferating Blood Vessels - van der Loos, Chris M. (Histochemical Society, 2010)
Nine commercially available vascular endothelial growth factor (VEGF) antibodies were investigated for their ability to immunostain vascular malformations (VMs) with or without immature capillary proliferation. First, all antibodies were optimized for their performance in IHC, with placenta and colon adenocarcinoma as positive control tissues. Five antibodies were regarded as unfit for VEGF immunostaining based on poor immunostaining criteria. Subsequently, Western blot analysis using VEGF rabbit polyclonal antibody (Thermo RB-9031) revealed a clear 45-kDa band in tissue extracts from VMs with immature capillary proliferation and a high Ki67-labeling index, whereas tissue extracts from mature VMs without microvascular proliferation and no Ki67-labeling index demonstrated only a very weak 45-kDa band. In contrast, two VEGF antibodies, including the popular Santa Cruz A-20, revealed bands at 45 kDa of similar intensity in tissue extracts from both types of VMs. Staining characteristics of the 45-kDa band were reflected in the results obtained in IHC. (J Histochem Cytochem 58:109–118, 2010)